Learning to cycle : the influence of individual constraints and of the training bicycle - Mercê, Cristiana Isabel André (2022)
The present thesis aimed to investigate an important motor milestone in children’s life, the process of learning to cycle, more specifically to: 1) systematically review the intervention programs for learning to cycle; 2) investigate different constraints that influence this learning process; 3) create and implement a learning to cycle intervention, and compare the learning process between the balance bike (BB) and the bicycle with lateral training wheels (BTW); 4) analyse the BB’s cycling patterns and investigate if velocity is a control parameter; 5) compare the motor variability during the learning process with BB and BTW. The methodology included a systematic review, one web-survey, a longitudinal intervention, and two cross-sectional studies. The systematic review pointed that it should be adopted a progressive cycle learning strategy, primarily using training bicycles and simpler exercises. The survey identified differences in the age of learning to cycle (ALC) according to the: training bicycle used, with the BB's approach revealing the lowest ALC; birth decade, which has decreased since 1970-79; physical activity, with people more active learning to cycle earlier; and birth order, with the younger children learning earlier than only children. The “L2Cycle” program was applied to 25 children (6.08±1.19 years), having a success rate of 88% (100%-BB, 75%-BTW). BB’s children needed fewer days to cycle independently (self-launch, ride and brake). Seven BB’s cycle patterns were categorized. After six sessions, children explored more cycling patterns and increased their global velocities. The results support that velocity is a probable control parameter. During the learning process, the BB allowed a greater motor variability than the BTW, leading to a faster adaptation to the traditional bicycle, which is a potential reason for its greater learning efficiency.